2023
DOI: 10.3390/su15097511
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Enzyme Hybrid with Nanomaterials: A Potential Cargo as Sustainable Biocatalyst

Abstract: With advancements in bionanotechnology, the field of nanobiocatalysts has undergone rapid growth and revolutionized various nanomaterials as novel and fascinating nanocarriers for enzyme immobilization. Nanotubes, nanofibers, nanopores, nanoparticles, and nanocomposites have been successfully developed and used as nanocarriers. The construction of robust nanobiocatalysts by combining enzymes and nanocarriers using various enzyme immobilization techniques is gaining incredible attention because of their extraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…Nanotechnology pretreatment methods have been considered the best option for delignification, as these pretreatment methods are cost-effective because the immobilized enzymes are easily retrievable and reusable [91,92]. Depending on the type of nanomaterial used, a few drawbacks of nanotechnology pretreatment methods include their potential poor dispersion abilities of some nanoparticles (due to the difficulty of dispersing in the aqueous solution, where hydronium ions are not effective) [93], and biocatalyst desorption could arise due to the weak bonds [94].…”
Section: Pretreatment Methods Of Lignocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Nanotechnology pretreatment methods have been considered the best option for delignification, as these pretreatment methods are cost-effective because the immobilized enzymes are easily retrievable and reusable [91,92]. Depending on the type of nanomaterial used, a few drawbacks of nanotechnology pretreatment methods include their potential poor dispersion abilities of some nanoparticles (due to the difficulty of dispersing in the aqueous solution, where hydronium ions are not effective) [93], and biocatalyst desorption could arise due to the weak bonds [94].…”
Section: Pretreatment Methods Of Lignocellulosementioning
confidence: 99%
“…The cost-effective operation of lignocellulose biorefinery will incline if these challenges are abated and all three constituents (cellulose, hemicellulose, and lignin) of lignocellulose are efficiently converted into value-added products. Nanotechnology, where enzyme immobilization is used in delignification, could be the best pretreatment technology for solving the bottlenecks of by-product inhibition [94]. Reports have shown that feedback inhibition can be minimized by removing sugars during saccharification using electrodialysis, avoiding cellobiose accumulation, and optimizing enzymatic activities during hydrolysis [220,221].…”
Section: Challenges and Alleviation Strategies In Upcycling Lignocell...mentioning
confidence: 99%
“…Recently, attempts have been made to develop catalytic systems that combine the features of biocatalysts and metallic nanomaterials [35,43]. Because of their small size, large surface area [44], and quantum size effects, metal-based nanomaterials, particularly noble metals such as gold, platinum, and palladium, are well suited for this purpose. These nanomaterials can facilitate charge transport, enzyme delivery, and the control of enzymatic activity.…”
Section: Metal Nanomaterialsmentioning
confidence: 99%
“…Compared to conventional matrices, nanocarriers feature an ease of surface modification, enhanced stability, and reusability [11,12]. Metallic nanoparticles have gained particular recognition due to their high surface-to-volume ratio, strength, reactivity, and chemical inertness [13,14]. One of the examples may be iron oxide nanoparticles, further distinguished by their superparamagnetic properties and biocompatibility, which were discussed by Mohamed et al [15] to immobilize horseradish peroxidase (HRP).…”
Section: Introductionmentioning
confidence: 99%